Pengembangan Media Papan Kantong Pintar (PAKAPIN) Untuk Minat Belajar Siswa Kelas IV Dalam Mata Pelajaran Pendidikan Pancasila - Safira, Al Fenia Dewi; Anshory, Ichsan; Danawati, Murtyas Galuh (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2024)
The development of PAKAPIN (Smart Pocket Board) media was motivated by problems that occurred at SDN Sisir 03 Batu among class IV students, namely the lack of use of media, too much material content and student learning outcomes that were less than optimal. The aim of the research is to develop PAKAPIN media material "The meaning and examples of Pancasila principles in everyday life" for class IV Pancasila Education subjects, totaling 20 students. This research is Research and Development (R&D) research using the ADDIE research model which consists of analysis, design, development, implementation and evaluation. The data collection techniques used were observation, interviews, questionnaires and documentation. The data that has been obtained will be analyzed using qualitative and quantitative data. The research results show that the PAKAPIN media is in accordance with the results of material expert validation, media validation results, student and teacher response results, and evaluation test results that meet the criteria. So it is concluded that the PAKAPIN media is suitable and effective for use as learning media in Pancasila Education subjects.